The impact of the mesoprefrontal dopaminergic system on the maturation of interneurons in the murine prefrontal cortex - Islam, K. Ushna S.; Blaess, Sandra (Frontiers in Neuroscience, 2024)
The prefrontal cortex (PFC) undergoes a protracted maturation process. This is true both for local interneurons and for innervation from midbrain dopaminergic (mDA) neurons. In the striatum, dopaminergic (DA) neurotransmission is required for the maturation of medium spiny neurons during a critical developmental period. To investigate whether DA innervation influences the maturation of interneurons in the PFC, we used a conditional knockout (cKO) mouse model in which innervation from mDA neurons to the mPFC (mesoprefrontal innnervation) is not established during development. In this mouse model, the maturation of parvalbumin (PV) and calbindin (CB) interneuron populations in the PFC is dysregulated during a critical period in adolescence with changes persisting into adulthood. PV interneurons are particularly vulnerable to lack of mesoprefrontal input, showing an inability to maintain adequate PV expression with a concomitant decrease in Gad1 expression levels. Interestingly, lack of mesoprefrontal innervation does not appear to induce compensatory changes such as upregulation of DA receptor expression in PFC neurons or increased innervation density of other neuromodulatory (serotonergic and noradrenergic) innervation. In conclusion, our study shows that adolescence is a sensitive period during which mesoprefrontal input plays a critical role in promoting the maturation of specific interneuron subgroups. The results of this study will help to understand how a dysregulated mesoprefrontal DA system contributes to the pathophysiology of neurodevelopmental disorders.